Efektivitas Penggunaan Media Pembelajaran Putaran Peluang Terhadap Hasil Belajar Peserta Didik Kelas VIII - Fatimatuzzahra, Nabilla; Khabibah, Siti; Saâ€™adah, Nihayatus (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This research is motivated by the monotonous learning at SMP Unggulan Al Madinah Diwek Jombang which causes student tend to be less interested in the learning process. It implies that the learning process cannot be effective. The purpose of this study is to describe the effectiveness of â€œPutaran Peluangâ€ learning media reviewed from the students responses and learning outcomes. The type of research method is Pre Experimental research with One-Shot Case Study design, while the research method uses descriptive analysis with quantitative approach. The population is all students of class VIII at SMP Unggulan Al Madinah Diwek Jombang and the sample is 21 students of class VIII B. Data are collected by test using posttest sheet and questionnaire using students respons qustionnair sheet. The results of this study were: (1) Percentage of classical student learning outcomes was 76.1% and (2) Percentage of students positive responses for the use of â€œPutaran Peluangâ€ learning media was 86.1%. It can be concluded that the use of â€œPutaran Peluangâ€ learning media is effective reviewed from studentsâ€™ learning outcomes.